2012
DOI: 10.1080/08927014.2012.702342
|View full text |Cite
|
Sign up to set email alerts
|

Silicone fouling-release coatings: effects of the molecular weight of poly(dimethylsiloxane) and tetraethyl orthosilicate on the magnitude of pseudobarnacle adhesion strength

Abstract: A series of poly(dimethyl siloxane) (PDMS)/silica nanocomposites were synthesized utilizing a sol gel method. The samples were evaluated using pseudobarnacle adhesion and tensile strength tests. The effects of the molecular weight of the PDMS and the size and structure of the silica domains on biofouling release and the mechanical behavior of the PDMS/silica materials were investigated. Three different molecular weights (18,000, 49,000 and 79,000 g mol 71 ) of hydroxyl-terminated PDMS (HT-PDMS) were used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Such unfilled silicone coatings, whether condensation or hydrosilylation cured, are mechanically weak. Strain to break is typically ≤20%. , Strain to break for silica reinforced resins such as Dow Corning T4 is ∼400%, but Xie found that the force to remove a rigid bonded object, P c‑s , is relatively high (0.21 MPa) . Similarly, we found that P c‑s for (Dow Corning Sylgard 184) was 0.15–0.30 MPa depending on thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Such unfilled silicone coatings, whether condensation or hydrosilylation cured, are mechanically weak. Strain to break is typically ≤20%. , Strain to break for silica reinforced resins such as Dow Corning T4 is ∼400%, but Xie found that the force to remove a rigid bonded object, P c‑s , is relatively high (0.21 MPa) . Similarly, we found that P c‑s for (Dow Corning Sylgard 184) was 0.15–0.30 MPa depending on thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements were conducted on thick films (∼ 200 μm) according to ASTM Standard D 5618. , Typically, an aluminous cylindrical stud with 10 mm in diameter and 10 mm in height was bonded to the elastomer surface using an epoxy adhesive (Araldite). After being cured for 3 days under ambient conditions, the maximal shear force was recorded by a force gauge (SUNDOO SH-500) when the stud was moved parallel to the substrate at a constant rate.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Lowering the modulus of an elastic foulant-release coating has been shown by several researchers as an effective deterrent against algal plants [33] and barnacles (or pseudo-barnacles) [20,34]. A significant decrease in detachment force was observed when the coating modulus was reduced 10-1000 times lower than the foulant modulus [20,33,34,[287][288][289]. Chaudhury et al observed that the attachment of Ulva sporelings (young plants) was reduced by approximately 80% when modulus of a PDMS coating was reduced 12-fold.…”
Section: (C) Macro-foulingmentioning
confidence: 99%